Clinical profile and outcome of patients with indeterminate acute liver failure - Nabi, Tauseef; Rafiq, Nadeema (International Journal Of Community Medicine And Public Health, 2020)
Background: Acute liver failure (ALF) is a rare medical emergency and devastating clinical syndrome associated with high mortality. Indeterminate ALF still forms a significant number of cases in India as well in the world. We aimed to determine the clinical profile and outcome of patients with indeterminate ALF. Methods: A total of 30 patients with a diagnosis of Indeterminate ALF were included in the study. The variables evaluated were demographic, signs and symptoms, biochemical parameters, severity of liver injury, outcome, complications and duration of hospital stay. Results: Overall mortality was 18 (60%). Majority of the patients were females (56.7%). Majority of patients (60%) had grade III and IV encephalopathy at the time of admission. The mean age in Survived group was 30.6±11.6 years and in Died group was 42.6±10.2 years (p=0.005). INR, bilirubin AST, ALT and creatinine were significantly higher in Died group than Survived group. Mean grade of coma was significantly higher in Died group than Survived group (p=0.010). MELD Score was significantly higher in Died group 35.8±6.7 than Survived group 27.5±5.8 (P = 0.001). Sepsis and renal failure occurred more frequently in Died group. Duration of hospital stay was also significantly more in Died group versus Survived group (p=0.003). Conclusions: Indeterminate ALF disproportionately affected young females. Mortality was as high as 60%. The marked difference in spontaneous survival can be explained by the severity of hepatic dysfunction on admission and more frequent complications.